2019
DOI: 10.1186/s12936-019-3041-2
|View full text |Cite
|
Sign up to set email alerts
|

A global analysis of National Malaria Control Programme vector surveillance by elimination and control status in 2018

Abstract: BackgroundMaintaining the effectiveness of the currently recommended malaria vector control interventions while integrating new interventions will require monitoring key recommended indicators to identify threats to effectiveness including physiological and behavioural resistance to insecticides.MethodsCountry metadata on vector surveillance and control activities was collected using an online survey by National Malaria Control Programmes or partner organization officials. Country and regional surveillance act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(49 citation statements)
references
References 9 publications
0
47
0
2
Order By: Relevance
“…Untuk mengidentifikasi kesenjangan dalam cakupan intervensi pengendalian vektor. 4 Untuk mencapai tujuan tersebut, diperlukan beberapa indikator yang menjadi dasar pelaksanaan surveilans vektor yang diharapkan, yaitu identifikasi vektor, densitas vektor, perilaku mencari darah, kesukaan menggigit di dalam/di luar rumah, kesukaan istirahat di dalam/di luar rumah, konfirmasi Plasmodium dalam nyamuk vektor dan habitat larva vektor, disamping hasil konfirmasi resistensi insektisida. Dengan mengintegrasikan indikator tersebut, diharapkan dapat digunakan untuk menetapkan strategi dan perencanaan pengendalian vektor sehingga diharapkan upaya pengendalian vektor dapat dilakukan secara efektif dan efisien.…”
Section: Kemajuanunclassified
See 1 more Smart Citation
“…Untuk mengidentifikasi kesenjangan dalam cakupan intervensi pengendalian vektor. 4 Untuk mencapai tujuan tersebut, diperlukan beberapa indikator yang menjadi dasar pelaksanaan surveilans vektor yang diharapkan, yaitu identifikasi vektor, densitas vektor, perilaku mencari darah, kesukaan menggigit di dalam/di luar rumah, kesukaan istirahat di dalam/di luar rumah, konfirmasi Plasmodium dalam nyamuk vektor dan habitat larva vektor, disamping hasil konfirmasi resistensi insektisida. Dengan mengintegrasikan indikator tersebut, diharapkan dapat digunakan untuk menetapkan strategi dan perencanaan pengendalian vektor sehingga diharapkan upaya pengendalian vektor dapat dilakukan secara efektif dan efisien.…”
Section: Kemajuanunclassified
“…Dengan mengintegrasikan indikator tersebut, diharapkan dapat digunakan untuk menetapkan strategi dan perencanaan pengendalian vektor sehingga diharapkan upaya pengendalian vektor dapat dilakukan secara efektif dan efisien. 4 Pada tahun 2017 Balai Besar Litbang Vektor dan Reservoir Penyakit (B2P2VRP), Badan Penelitian dan Pengembangan Kesehatan (Badan Litbangkes) melakukan Riset Khusus Vektor dan Reservoir Penyakit (Rikhus (rikhus) vektora, koleksi lapangan nyamuk dan jentik, prosedur deteksi melekuler plasmodium dan analisis pakan darah dilakukan dengan menggunakan pedoman Rikhus vektora. Hasil studi menunjukkan bahwa Anopheles kochi dan Anopheles tesselatus, yang masing-masing ditemukan di eksoistem non hutan dekat pemukiman dan pantai dekat pemukiman ditemukan positif mengandung Plasmodium falciparum di Kabupaten Jembrana, Bali.…”
Section: Kemajuanunclassified
“…Algorithms for representative sampling across geographic areas for adults and larvae as well as de ning /stratifying receptivity are essential. However, a recent global assessment of vector surveillance activities by NMCPs revealed that routine surveillance of key indicators is limited and that entomological data is even less so used to inform programmatic decisions [8]. This suggests that programs must react to losses in program effectiveness rather than being proactive in responding to potential threats as they arise, such as behavioural and physiological resistance to insecticides.…”
Section: Algorithms For Representative Samplingmentioning
confidence: 99%
“…A global analysis of NMCP vector surveillance by elimination and control status in endemic countries was conducted utilizing an online survey instrument [8]. The survey included an evaluation of national malaria control program capacity for vector surveillance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation